O1-S01.04 Suboptimal repeat testing of women with positive chlamydia tests in the USA, 2008–2010. (10th July 2011) - Hoover, K; Tao, G; Body, B; Nye, M; Kent, C
Abstract : Background: Women treated for chlamydia have a high prevalence of infection several months later, likely caused by reinfection from an untreated or new infected sex partner. To prevent potential adverse outcomes of chlamydia, US guidelines recommend repeat testing 3 months after treatment, regardless of partner treatment. If retesting at 3 months is not possible, women should be retested at their next clinical encounter within 12 months. A chlamydia test-of-cure is also recommended for all infected pregnant women 3–4 weeks after treatment. We assessed adherence to retesting guidelines using data from a US laboratory corporation that has a large share of the US market. Methods: Among tests performed from June 2008 to May 2010, we estimated the percentage of women who were retested ≥3 weeks later by test result, age and pregnancy status. We also estimated the positivity rate among repeat chlamydia tests and the mean time between an initial test and the first repeat test. We assumed that for each woman in the database all chlamydia tests during the study period were performed by this laboratory corporation. Results: Among 2.90 million chlamydia tests performed in 1.77 million women, 4.0% (114 963) were positive. Among the 1.77 million women with tests, 1.34 million (75.7%) had only a single test and 0.43 million (24.3%) had at least one repeat test. If an initial test was positive, 48.6% were retested compared to 23.5% if the initial test was negative (p<0.01); a repeat test was more likely to be positive in women with an initial positive test (13.3%) than a negative one (3.3%) (p<0.01). The mean time interval between the initial and repeat test was shorter if the initial test was positive (117 days) than negative (149 days). Women aged 15–24 years with a positive test had a lower retesting rate than those aged 25–34 years (46.8% vs 53.3%). The percentage of women with a positive test who were retested differed significantly by pregnancy status (60.0% pregnant vs 44.2% nonpregnant), and pregnant women had a repeat test within 93 days compared to 125 days in nonpregnant women. Conclusions: These data from a large laboratory corporation provide insight into chlamydia testing practices among women in the USA, and suggest suboptimal adherence to retesting recommendations for both pregnant and nonpregnant women. These data can be useful to monitor the effectiveness of interventions to improve follow-up testing of women with chlamydia.